Ecology-faunistic and zoogeographic characteristic of Hemiptera of aridic hollows of internal mountain Daghestan - D. D. Magomedova (Юг России: экология, развитие)
According to the degree of areal weatness we have defined ecological groups of Hemiptera: gigrophils, mezophils and cserophils. 59 % of total numbers are mezophils. 101 species of hemiptera, located on the studied territory are combined according to belt-sector and provincial principiles in 23 types and 7 areal groups.